Inovation Strategy and External Support for Small Medium Enterprise’s Survival in Covid Era - Suparno (Journal of Research in Business, Economics, and Education, 2021)
Researchers have emphasized that SMEs are often the enterprises most affected by economic crises. Therefore, a socioeconomic crisis related to people’s health such as the COVID-19 pandemic can be expected to have dire effects on SMEs because these businesses require strong connections with people, whether they are customers or suppliers. To protect this vital sector from collapse due to the COVID-19 crisis, many governmental and nongovernmental organizations (NGOs) have provided various forms of support to SMEs. Governments have adopted several policies that will mitigate the negative effects of this crisis. SMEs have received some financial support from local and international NGOs and financial institutions during the COVID-19 crisis. Additionally, SME owners have adopted a number of practices and strategies to confront the ramifications of the crisis. Innovation is the core factor behind the survival and continuity of enterprises; it supports the company’s expansion and growth and enhances the enterprise’s future success.